2014
DOI: 10.3390/molecules191220709
|View full text |Cite
|
Sign up to set email alerts
|

Chemically Synthesized Glycosides of Hydroxylated Flavylium Ions as Suitable Models of Anthocyanins: Binding to Iron Ions and Human Serum Albumin, Antioxidant Activity in Model Gastric Conditions

Abstract: . Both pigments inhibit heme-induced lipid peroxidation in mildly acidic conditions (a model of postprandial oxidative stress in the stomach), the colorless (chalcone) forms being more potent than the colored forms. Finally, P1 and P2 are moderate ligands of human serum albumin (HSA), their likely carrier in the blood circulation, with chalcones having a higher affinity for HSA than the corresponding colored forms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
3
11
0
Order By: Relevance
“…In particular, our results indicate a larger stability of the metal‐cyanin complex with Cu(II), Δ b E = −52.04 kcal mol −1 /Δ b G = −37.59 kcal mol −1 , than with Zn(II), Δ b E = −31.74 kcal mol −1 /Δ b G = −19.65 kcal mol −1 , in agreement with what has been observed experimentally . Also, it has been found that binding to Fe(II) goes more slowly than with Fe(III) and that complexation with the latter goes faster than with Al(III), which can be pretty well correlated with our results.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…In particular, our results indicate a larger stability of the metal‐cyanin complex with Cu(II), Δ b E = −52.04 kcal mol −1 /Δ b G = −37.59 kcal mol −1 , than with Zn(II), Δ b E = −31.74 kcal mol −1 /Δ b G = −19.65 kcal mol −1 , in agreement with what has been observed experimentally . Also, it has been found that binding to Fe(II) goes more slowly than with Fe(III) and that complexation with the latter goes faster than with Al(III), which can be pretty well correlated with our results.…”
Section: Resultssupporting
confidence: 91%
“…[9] However, some of our kcal mol −1 , in agreement with what has been observed experimentally. [33] Also, it has been found [29] that binding to Fe(II) goes more slowly than with Fe(III) and that complexation with the latter goes faster than with Al(III), which can be pretty well correlated with our results.…”
Section: Metal Binding Cyanin Affinitiessupporting
confidence: 88%
See 2 more Smart Citations
“…Whereas anthocyanins rapidly bind to aluminum and ferric ions, they weakly interact with ferrous ions promoting their autoxidation to Fe III (Bayer et al, 1966;Bittar et al, 2014). Under slightly acidic conditions, a huge excess of aluminum ions (metal to anthocyanin ratio of >100:1) is required to achieve blue hues (Sigurdson and Giusti, 2014).…”
Section: Structure and Fundamentals Of Anthocyanin-metal Chelate Formmentioning
confidence: 99%